Punishment - Canton, Robert (Abingdon, Oxon ; New York, NY : Routledge, 2022)
This book explores the concept of punishment: its meaning and significance, not least to those subject to it; its social, political and emotional contexts; its role in the criminal justice system; and the difficulties of bringing punishment to an end. It explores how levels of criminal punishment could and should be reduced, without compromising moral standards, public safety or the rights of victims of crime. Core contents include: Why punishment matters, the salience of emotions in its various discourses and the role of culture. The politicisation of punishment and legitimacy. The penal system, the prominence of the prison in research on punishment and the role of community sanctions. The aims of punishment, its limits and the role of power. The ethics of punishment and human rights. Punishment and social order. This book is essential reading for all criminologists, as well as students taking courses on punishment, penology, prisons and the criminal justice system.
Keywords: Punishment -- Philosophy; Punishment; Justice; Common good; LAW / Criminal Law / Sentencing; LAW / Criminal Procedure; SOCIAL SCIENCE / Criminology